Solve this equation: – 7x + 12 – 2x = 23 + 13x -7x+12-2x = 23+13% Step 1: Simplify by combining like terms that are on the

Question

Solve this equation: – 7x + 12 – 2x = 23 + 13x
-7x+12-2x =
23+13%
Step 1: Simplify by combining like terms that are on the
same side of the equation. Which terms can be
combined? -7x and -2x
– 9x+12 =
-23
23+13x
-23
Step 2: Both sides of the equation contain a variable term. It
is possible to isolate the variable term on either the
left or right side of the equation. How would you like
to isolate the variable term?
-9x-11 =
+ 9x
+13x
+9x
-11 =
+ 22
+22x
= 22
Subtract 23
from both sides of the equation.
Step 3: Isolate the variable term on one side of the equation
by adding 9x to
both sides of the equation.
Correct Dividing both sides by 22
isolates x

in progress 0
Isabella 1 month 2021-09-14T14:54:14+00:00 1 Answer 0

Answers ( )

    0
    2021-09-14T14:55:54+00:00

    Answer:subtract 23

    Step-by-step explanation:

Leave an answer

45:7+7-4:2-5:5*4+35:2 =? ( )